Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have: $X = <\mathbb R^2, ||(x,y)|| = \sqrt{4x^2+y^2}>, L = \{(2x,3x), x \in\mathbb R\}, $

$\phi_0 \in L^* : \phi_0 (2x,3x) = -2x$

I need to extend $\phi_0$ on $X$ without changing norm (norm should stay the same). How can I do it?

share|improve this question
1  
i think by "expand" you mean "extend".......... –  Fermat May 13 at 7:41
1  
@Hamid Oh, thanks –  michaeluskov May 13 at 7:45
1  
I'm not clear what you're doing on line 2: the domain of $\phi_0$ is elements of the form $(2x,3x)$. How is $(0,2x)$ of this form? Is this a typo? –  Rudy the Reindeer May 13 at 10:21
    
@MattN. oh, this is mistake. I edited post. –  michaeluskov May 13 at 14:42

1 Answer 1

Note first that $X$ is an inner-product space. The norm is given by the inner product $$ \langle (x,y),(w,z)\rangle = 4xw+yz. $$

Let us calculate the norm of $\phi_0$. We have $$ \|\phi_0\|=\sup\left\{\frac{|\phi_0(2x,3x)|}{\|(2x,3x)\|}:\ x\ne0 \right\} =\sup\left\{\frac{|-2x|}{\sqrt{16x^2+9x^2}}:\ x\ne0 \right\} =\sup\left\{\frac{2|x|}{5\,\sqrt{x^2}}:\ x\ne0\right\}=\frac25. $$ If we try to extend $\phi_0$ as $\phi(x,y)=-x$, then the norm is not preserved: $$ \|\phi\|=\sup\left\{\frac{|\phi(x,y)|}{\|(x,y)\|}:\ (x,y)\ne(0,0) \right\} =\sup\left\{\frac{|-2x|}{\sqrt{4x^2+y^2}}:\ (x,y)\ne(0,0) \right\} =\sup\left\{\frac{2|x|}{\sqrt{4x^2+y^2}}:\ (x,y)\ne(0,0) \right\}=1 $$ (the sup is attained when $y=0$).

The way to extend $\phi_0$ without enlarging the norm is to define it as zero on the orthogonal complement of $L^*$. As the dimension of $X$ is $2$ and the dimension of $L^*$ is $1$, the dimension of the orthogonal is also $1$. If $(z,w)\perp(2x,3x)$, we have $$ 0=\langle(z,w),(2x,3x)\rangle=8xz+3xw=(8z+3w)x. $$ As this should be zero for all $x$, we get $8z+3w=0$, or $w=-8z/3$. So a basis for $(L^*)^\perp$ is given by $\{(3,-8)\}$. Then we can define $$ \phi(\alpha (2,3)+\beta(3,-8))=-2\alpha. $$ If we want to express $\phi$ in terms of a single pair $(x,y)$, we need to write $$ (x,y)=\frac{8x+3y}{25}\,(2,3)+\frac{3x-2y}{25}\,(3,-8), $$ so $$ \phi(x,y)=-2\,\frac{8x+3y}{25}=\frac{-16x-6y}{25}. $$ A little multivariable calculus can show that $\|\phi\|=2/5$, as desired.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.